В решении.
Объяснение:
Знайти значення виразу (х²+7)(х⁴-7х²+49)-х⁴-0,25х, якщо х=16;
(х² + 7)(х⁴ - 7х² + 49) - х⁴ - 0,25х =
В первых двух скобках развёрнута сумма кубов, свернуть по формуле:
= (х²)³ + 7³ - х⁴ - 0,25х =
= х⁶ + 7³ - х⁴ - 0,25х =
=16⁶ + 343 - 16⁴ - 0,25 * 16 =
= 16⁶ + 343 - 16⁴ - 4 =
= 16⁶ - 16⁴ + 339 =
=16 777 216 - 65 536 + 339 = 16 712 019.
В решении.
Объяснение:
Знайти значення виразу (х²+7)(х⁴-7х²+49)-х⁴-0,25х, якщо х=16;
(х² + 7)(х⁴ - 7х² + 49) - х⁴ - 0,25х =
В первых двух скобках развёрнута сумма кубов, свернуть по формуле:
= (х²)³ + 7³ - х⁴ - 0,25х =
= х⁶ + 7³ - х⁴ - 0,25х =
=16⁶ + 343 - 16⁴ - 0,25 * 16 =
= 16⁶ + 343 - 16⁴ - 4 =
= 16⁶ - 16⁴ + 339 =
=16 777 216 - 65 536 + 339 = 16 712 019.